ASSESSING SPEECH THROUGH ENGLISH DEBATE TO IMPROVE SPEAKING ABILITY OF UNIVERSITY STUDENTS - Hariyanto Hariyanto; Eka Setya Budi; Ali As'ad (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2019)
The assessment of oral production and good English speaking ability can be success indicators for students of English study program at UNISNU Jepara University to be qualified teachers. However, students of fourth semester still found weaknesses to acheive. This research was conducted to improve their learning achievement in speaking skill and assessment. It made use a classroom action research design through communicative approach type academic debate and oral production test. The initial condition of students speaking skill was categorized as poor level because the mean score of pretest was 50. The application of cyclic process, which consisted of two cycles, involved four steps: planning, action, observation and reflection. The increasing ability in each cycle could be seen from their scores either individual or team. The individual score of each session for three aspects of debate had gradually increased. The mean score of cycle I was 72 which can be categorized as sufficient level and cycle two was 83 which meant at very good level. The students’ responses were also positive after this learning model was applied. They also admitted that they had learned many things which were related to their skill in controlling emotion, practicing speaking ability, enriching vocabularies, and arguing in positive attitude.  Based  on  the  finding  and  discussion,  the  type academic  debate  and  oral  production  assessment  can  improve  students’  ability in speaking English.